Getting Up to Speed on the Financial Crisis: A One-Weekend-Reader's Guide - Gorton, Gary; Metrick, Andrew (Journal of Economic Literature, 2012)
All economists should be conversant with “what happened?” during the financial crisis of 2007–09. We select and summarize sixteen documents, including academic papers and reports from regulatory and international agencies. This reading list covers the key facts and mechanisms in the build-up of risk, the panics in short-term-debt markets, the policy reactions, and the real effects of the financial crisis. (JEL E32, E44, E52, G01, G21, G28)